Densification and electrical conductivity of fast fired manganese-doped ceria ceramics - Pereira, G. J.; Castro, RHR; de Florio, D. Z.; Muccillo, ENS; Gouvea, D. (Elsevier B.V., 2005)
Reactive pure and manganese-doped (5% and 10 at.%) ceria nanosized powders were prepared by the polymeric precursor technique. Physical properties of powder materials were studied by X-ray diffraction, nitrogen adsorption, and diffuse reflectance infrared Fourier transform spectroscopy. Characterization of powder compacts after fast firing at 1200 degrees C for 5 min was carried out by scanning electron microscopy and impedance spectroscopy measurements. The bulk apparent density of sintered pellets was determined for pellets of different compositions sintered at 1200 degrees C. A gradual decrease of the particle size occurs with increasing doping content. Relatively high values of apparent density were obtained after fast firing doped specimens at 1200 degrees C. DRIFT spectra evidence that a fraction of Mn ions was segregated onto particles surface. The electrical resistivity of sintered pellets reveals different mechanisms of conduction depending on the Mn content. (C) 2005 Elsevier B.V All rights reserved.
Keywords: CeO(2); DRIFT; fast firing; electrical properties; electroceramics; impedance spectroscopy